THE REPRESENTATION OF POWER IN JOKO WIDODO’S SPEECH - Serius Afandi Bukit; Muhammad Natsir (State University of Medan, 2016)
This study aims at figuring out how power can be seen in the Joko Widodo’sspeech. what is the dominant type of power used in Joko Widodo’s speech andwhy. It deals with the tenor which is focused on the power. This research useddescriptive qualitative method in which the writer analized the data by describingthe power that realized in the Joko Widodo’s speech. The data of this study takenfrom article in the internet. The data were the speech of Joko Widodo, it takesfrom different four speech that Jokowi have done in different place and situation.The writer found that the power in Joko widodo’s speech mostly is equal whileJokowi speak in the international situation.